How do apathetic and depressive symptoms relate to functional capacity? A cross-sectional survey among community-dwelling middle-aged and older adults in Japan - Hikaru Oba; Akira Kanda; Kazushige Ihara; Asano Tanabu; Hiroshi Shimoda (BMC, 2024)
Abstract Background Apathetic and depressive symptoms are frequently observed among older adults, and are risk factors for functional decline and dementia progression. However, how these symptoms influence functional capacity remains unclear. This study investigated the relationship between apathetic and depressive symptoms and functional capacity, considering the interaction between apathetic and depressive symptoms. Methods A cross-sectional questionnaire survey targeting community dwelling middle-aged or older adults was conducted. We sent a questionnaire to 984 individuals and received 320 responses. Data with missing values and participants aged under 50 were excluded, resulting in 212 participants (88 men and 124 women, mean age = 73.4 ± 9.3 years). Apathetic symptoms were evaluated using the Dimensional Apathy Scale (J-DAS), which comprises executive, emotional, and cognitive and behavioral initiation aspects of apathy. Depressive symptoms were evaluated using the Geriatric Depression Scale (GDS). Functional capacity was assessed using the Japan Science and Technology Agency Index of Competence, which comprises technology usage, information practice, life management, and social engagement. Results Mean score of each J-DAS factor and GDS was 5.3 ± 3.4 (executive), 12.0 ± 3.0 (emotional), 11.8 ± 5.1 (initiation), and 4.5 ± 3.3, respectively. The emotional and initiation aspects of J-DAS were significantly associated with information practice (β = -0.15, p < .05 for emotional; β = -0.27, p < .001 for initiation) and life management (β = -0.20, p < .01 for emotional; β = -0.22, p < .01 for initiation) in functional capacity. GDS was associated only with social engagement (β = -0.31, p < .001). Although the interaction between the initiation factor of J-DAS and GDS was significantly associated with life management (β = -0.16, p < .05), the R 2 change was insignificant. The emotional factor of J-DAS was associated with technology usage (β = -0.13, p < .05), although less strongly than age. The executive factor of J-DAS had insignificant associations with all aspects of functional capacity. Conclusions Apathetic and depressive symptoms are independently, rather than interactively, associated with different aspects of functional capacity. As older adults with apathetic or depressive symptoms might struggle to seek help from public health services, they should be targeted with active interventions from healthcare professionals.